PENGARUH SUBTITUSI TEPUNG IKAN OLEH TEPUNG MAGGOT BLACK SOLDIER FLY (BSF) DALAM PEMBUATAN PAKAN TERHADAP NILAI KONSUMSI PAKAN, HDP DAN BERAT TELUR AYAM PETELUR PERIODE LAYER - Widigdyo, Anang; Putra, Aditya Wirawantoro; Normawanti, Rani Arifah; Mujiono, M.; Nalendra, Adimas Ketut (JAMI: Jurnal Ahli Muda Indonesia, 2023)
Objective This study aims to determine the effect of using BSF maggot flour as a substitute for fish meal in feed on the value of feed consumption, HDP and egg weight in layer chickens.. Materials and Methods. The research design used a completely randomized design with 5 treatments and 5 replications. Treatment 1 (P1) in this study was a control treatment using factory feed. P2 Fish meal 20% with 80% basal feed; P2 Fish meal 15% with 5% BSFL (Maggot) flour and 80% Basal Feed; P3 fish meal 10% with 10% BSFL flour and 80% basal feed, and P4 fish meal 5% with 15% BSFL flour. Conclusion. The results of the observations showed that the use of maggot flour as a substitute for fish meal in the manufacture of feed did not significantly differ from feed consumption, HDP and egg weight of laying hens.